Addition of cobalt nanoparticles into Sn-3.8Ag-0.7Cu lead-free solder by paste mixing - Tay, S.L.; Haseeb, A.S. Md. Abdul; Johan, M.R. (2011)
Purpose - The purpose of this paper is to investigate the effects of addition Co nanoparticles on the characteristic properties of Sn-3.8Ag-0.7Cu solder. Design/methodology/approach - Cobalt (Co) nanoparticles were added to Sn-Ag-Cu solders by thoroughly blending various weight percentages (0-2.0 wt) of Co nanoparticles with near eutectic SAC387 solder paste. Blending was done mechanically for 30 min to ensure a homogeneous mixture. The paste mixture was then reflowed on a hot plate at 250 degrees C for 45s. The melting points of nanocomposite solder were determined by differential scanning calorimetry. Spreading rate of nanocomposite was calculated following the JIS Z3198-3 standard. The wetting angle was measured after cross-sectional metallographic preparation. Findings - No significant change in melting point of the solder was observed as a result of Co nanoparticle addition. The wetting angles of the solder increased with the addition of nanoparticles, while the spreading rate decreased. Although the wetting angle increased, the values were still within the acceptable range. Scanning micrograph observations revealed that the as-solidified microstructure of the composite solder was altered by the addition of Co nanoparticles. Microhardness of the solders slightly increased upon Co nanoparticles addition to SAC387. Originality/value - The paper demonstrates that a simple process like paste mixing can be used to incorporate nanoparticles into solder.